Writing a journal paper : The structure behind it - Ting, Su Hie (2009)
This workshop aims to provide explicit guidance on the writing of a research article, from the organization of the abstract to the conclusion. The theoretical knowledge for the workshop is drawn from decades of research on the rhetorical structure and conventions of research articles in various disciplines, including a comparison of the research writing of native speaker and non·native speakers of English. The workshop begins with a presentation of the structure of a research article in terms of the moves and steps of different sections of the article (Abstract, Introduction, Method, Results, Discussion, Conclusion). Following this, participants are taken through an analysis of the structure of some sample research articles in the science and arts to develop their awareness of the rhetorical structure of a research article. Finally, participants are given hands-on practice in analysing either their own or provided draft research articles in order to identify weak links in the article for improvement. This workshop is designed to help academics develop critical knowledge of writing conventions of research articles to help them compete for research space and justify their work in an international research discourse community.